PERSEPSI MASYARAKAT SEKITAR HUTAN DESA SEPAHAT KECAMATAN MENJALIN TERHADAP PERTAMBANGAN EMAS TANPA IZIN (PETI) - Afriana, Novi; Roslinda, Emi; Ekyastuti, Wiwik (JURNAL HUTAN LESTARI, 2015)
Illegal gold mining, has been going on for many years in Sepahat village. Illegal gold mining is very difficult to stopped because it is the main livelihood of the community. The research purposes were to determine the community perception of illegal gold mining and to determine the relationship of individual factors. This research executed with survey method. Data were analyzed descriptively and the inter-relationship seen with Chi Square analysis. Caracteristics of illegal mining communities are dominated by adulthood, rubber farmer as a livelihoods, and the level of education are elementary school. Community perception is neutral on illegal gold mining. This is because the income from illegal gold mining can meet their needs. The level of age, knowledge, and income are not significantly associated with the community perception on illegal gold mining. Keywords: Community perception, illegal gold mining.